Understanding socialbot behavior on end hosts. (February 2017) - He, Yukun; Li, Qiang; Cao, Jian; Ji, Yuede; Guo, Dong
Server-side socialbot detection approaches can identify malicious accounts and spams in online social networks. However, they cannot detect socialbot processes, residing on user hosts, which control these accounts. Therefore, new approaches are needed to detect socialbots on hosts. The fundamental to design host-side detecting approaches is to gain an insight into the behaviors of socialbots on host. In this article, we analyzed a series of representative socialbots in depth and summarized the typical features of socialbot behaviors. We proposed a new approach to defense against socialbots on end host. The contributions of this article are threefold: (1) our analysis approach can be used for reference during analyzing new socialbots in the future; (2) we provide several behavior features of socialbots on hosts, including network flow through which socialbots communicate with botmasters through the online social network, system calls via which socialbots conduct an activity, and process information of socialbots running on hosts. These features can be used by someone to design approaches to identifying socialbots on a host; (3) our proposed detection approach can effectively distinguish between a socialbot and a benign application on end hosts.